Design of Government Organs to Achieve Regulatory Reform in Indonesia: Learning from Malaysia and Vietnam - Eka Dewi, Natalia Nanda; Sjarif, Fitriani Ahlan (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
In an attempt to reform regulation in Indonesia, this study looks at best practice designs that have been adopted in Malaysia and Vietnam in order to determine the optimum government organ in the field of law. Indonesia ought to take a cue from the successful regulatory reform initiatives in Malaysia and Vietnam and establish dedicated agencies that have enhanced the calibre of legislation and regulations. This essay uses a normative legal approach that is descriptive as well as prescriptive. The talk explains how government bodies that deal with a variety of laws are designed to meet the specific demands of the several nations that make up the group. Vietnam adopts the institution's design, which is the assembly in the field of laws and regulations, which holds the position of the highest representative organ, while Malaysia adopts the design of a particular institution with the primary function of guaranteeing the entire process of forming laws and regulations that apply centrally. As per Law Number 15 of 2019 regarding Amendments to Law Number 12 of 2011 regarding the Establishment of Legislation, Indonesia is recommended to establish ministries or institutions whose specific design and existence must be determined as close to the center of government as possible.